2016
DOI: 10.3390/biology5040038
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as a Signaling Molecule That Regulates Exercise-Induced Adaptations

Abstract: Lactate (or its protonated form: lactic acid) has been studied by many exercise scientists. The lactate paradigm has been in constant change since lactate was first discovered in 1780. For many years, it was unfairly seen as primarily responsible for muscular fatigue during exercise and a waste product of glycolysis. The status of lactate has slowly changed to an energy source, and in the last two decades new evidence suggests that lactate may play a much bigger role than was previously believed: many adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 80 publications
1
99
0
3
Order By: Relevance
“…Recently, Tsukamoto et al [11] demonstrated that intraperitoneal injection of lactate in mice elicited a hypertrophic response compared to controls; importantly, lactate levels were similar to those induced by moderate repletion RT protocols, suggesting a potential physiological role. Many molecular mechanisms involved in this process are currently unknown but may be related to the relationship between [bLa -] and muscle anabolism; therefore, the mechanisms behind these adaptations have not yet been sufficiently identified, and further research is needed to support this relationship [12]. Notably, metabolite accumulation alone does not seem sufficient to substantially increase muscle mass in humans; however, it may have a positive additive effect on anabolic processes due to its capacity to generate an increase in muscle activation [13], promote the recruitment of high-threshold motor units [14], and trigger the production of myokines and reactive oxygen species that have been implicated in hypertrophic adaptations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tsukamoto et al [11] demonstrated that intraperitoneal injection of lactate in mice elicited a hypertrophic response compared to controls; importantly, lactate levels were similar to those induced by moderate repletion RT protocols, suggesting a potential physiological role. Many molecular mechanisms involved in this process are currently unknown but may be related to the relationship between [bLa -] and muscle anabolism; therefore, the mechanisms behind these adaptations have not yet been sufficiently identified, and further research is needed to support this relationship [12]. Notably, metabolite accumulation alone does not seem sufficient to substantially increase muscle mass in humans; however, it may have a positive additive effect on anabolic processes due to its capacity to generate an increase in muscle activation [13], promote the recruitment of high-threshold motor units [14], and trigger the production of myokines and reactive oxygen species that have been implicated in hypertrophic adaptations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the meat quality of Nellore calves, Zorzi et al (2013) could verify that there was a close relationship between pH and other qualitative traits. After slaughter, the residual metabolic activity of the muscle causes the degradation of glycogen to lactate, which dissociates to lactic acid, causing pH to decrease (Nalbandian and Takeda 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that the lactate produced during exercise acts as a regulator of the accumulation of H + ions in the intramuscular space, because it is easily transported to the interstitial space or to the blood, captured by other cells, and metabolized in the Krebs cycle or in the gluconeogenic pathway. 37 Thus, the results found on the effects of GI in the pre-exercise meal on lactate levels seem irrelevant.…”
Section: Discussionmentioning
confidence: 99%